2012
DOI: 10.1155/2012/521612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Laser Acupuncture and Cupping with Ryodoraku and Visual Analog Scale on Low Back Pain

Abstract: The purpose of this study was to evaluate the effect of laser acupuncture (LA) and soft cupping on low back pain. In this study, the subjects were randomly assigned to two groups: active group (real LA and soft cupping) and placebo group (sham laser and soft cupping). Visual analog scale (VAS) and Ryodoraku were used to evaluate the effect of treatment on low back pain in this trial. Laser, 40 mW, wavelength 808 nm, pulse rate 20 Hz, was used to irradiate Weizhong (BL40) and Ashi acupoints for 10 minutes. And … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 22 publications
2
73
0
2
Order By: Relevance
“…Some trials did not fully describe details of their inclusion criteria for chronicity22 23 or specificity 2223 31 In trials where the mean baseline duration of pain was reported, this was categorised as ‘shorter’24 26 27 30 (average range 4.6–27   months) or ‘longer’18 21 25 28 29 34 (49   months to 13   years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some trials did not fully describe details of their inclusion criteria for chronicity22 23 or specificity 2223 31 In trials where the mean baseline duration of pain was reported, this was categorised as ‘shorter’24 26 27 30 (average range 4.6–27   months) or ‘longer’18 21 25 28 29 34 (49   months to 13   years).…”
Section: Resultsmentioning
confidence: 99%
“…Five trials were classified as LA studies18 21 28 31 34 (table 2). Three of these trials used smaller doses of 0.2–1.1 J/point 18…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we were not able to determine the differences that contributed to the successful treatment. Nevertheless, further two RCTs showed a positive response for low back pain treated with LA [36,37].…”
Section: Low Back Painmentioning
confidence: 97%
“…The addition of manipulating methods such as lifting, thrusting, and twisting can further enhance the efficiency of acupuncture [29]. It has also been indicated that the application of laser acupuncture at acupoints can result in similar effects [30,31]. Currently, the most commonly used instrument to evaluate the quality of meridians in the human body is a Ryodoraku device [32,33].…”
Section: Effect Of Lifting and Thrusting On The Meridiansmentioning
confidence: 99%
“…The efficacy of laser acupuncture on meridians has already been validated [24,30]; however, the effects of adding the manipulating methods like traditional acupuncture has not yet been discussed. In this study, we adopted a self-developed laser-acupuncture system to explore the effects on meridians by using the manipulating methods of lift and thrust and compared the effects to those of laser acupuncture that does not employ these methods.…”
Section: Effect Of Lifting and Thrusting On The Meridiansmentioning
confidence: 99%